2002
DOI: 10.1097/00005537-200207000-00029
|View full text |Cite
|
Sign up to set email alerts
|

The 11th Nerve Syndrome in Functional Neck Dissection

Abstract: The post-surgical variable clinical picture of shoulder disability is related not only to the accessory nerve injury, but also to the secondary glenohumeral stiffness resulting from the scapulohumeral girdle muscles weakness and postoperative forced immobility. Physical therapy aimed to early recover passive motion and to avoid the occurrence of joint fibrosis has been shown to have a real contributory role in decreasing shoulder complaints and improving the patients' QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0
9

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 15 publications
0
54
0
9
Order By: Relevance
“…22,23 In the standard postoperative care, range of motion of the shoulder and pain must be evaluated, and, when indicated, a specific rehabilitation program may be prescribed. 24 The significantly worse outcome for limitations because of physical problems in the patient group compared with the control group shows that physical rehabilitation may be important; but the reduced social functioning and importance of depression show that, in addition to training of physical skills, psychosocial rehabilitation should also be addressed. 25 Notable was the significantly better outcome in the pain domain for the patients compared with the control group.…”
Section: Discussionmentioning
confidence: 97%
“…22,23 In the standard postoperative care, range of motion of the shoulder and pain must be evaluated, and, when indicated, a specific rehabilitation program may be prescribed. 24 The significantly worse outcome for limitations because of physical problems in the patient group compared with the control group shows that physical rehabilitation may be important; but the reduced social functioning and importance of depression show that, in addition to training of physical skills, psychosocial rehabilitation should also be addressed. 25 Notable was the significantly better outcome in the pain domain for the patients compared with the control group.…”
Section: Discussionmentioning
confidence: 97%
“…electrophysiological evaluations have shown that, despite the nerve's anatomical integrity, the risk is even greater whenever the neck's posterior triangle is involved (level V) 1,[15][16][17] . The muscles' denervation potentials become characteristic after two to three weeks of the lesion, first on the proximal muscles, later on the distal ones.…”
Section: Discussionmentioning
confidence: 99%
“…There was also an improvement in overall QOL as assessed by the SF-36 health survey [ 13 ] . A signifi cant improvement in QOL was also seen in laryngectomy patients who had undergone a contemporaneous neck dissection when receiving a rehabilitation protocol of passive and active shoulder exercises [ 46 ] .…”
Section: Laryngectomy Patientsmentioning
confidence: 91%